Comparison of GPS-TEC observations over Addis Ababa with IRI-2012 model predictions during 2010–2013. Issue 8 (15th October 2015) - Akala, A.O.; Somoye, E.O.; Adewale, A.O.; Ojutalayo, E.W.; Karia, S.P.; Idolor, R.O.; Okoh, D.; Doherty, P.H.
Highlights We characterized GPS-TEC over Addis Ababa, Ethiopia during 2010–2013. TEC over Addis Ababa recorded minimum values at 0400–0500 LT and maximum at 1400–1500 LT. TEC recorded the highest values during equinoxes and the least during June solstices. TEC increases with solar activity, and of all the three options of IRI-2012, NeQuick was most accurate.